Salienz und Pertinenz – Zur subjektiven Dialektalität remanenter Regionalismen des Mittelbairischen - Kiesewalter, Carolin (Linguistik Online, 2014)
As we know, speech perception and production are strongly influenced by sign-specific "socio-pragmatic indexicality" (cf. Purschke 2014), that is, by the mental conceptions (of meaning, style etc.) people associate with individual linguistic features. I assume that, in German-speaking areas, the "subjective (notion of the) dialectality" of a non-standard feature represents a basic form of socio-pragmatic indexicality and is closely connected to language variation and change, in that the more regionalisms are regarded as non-standard features, the more they vary synchronically and diachronically. Following Purschke (2014), I define the subjective dialectality of regionalisms as being based on their feature-specific "salience" and "pertinence", that is, on both the pure awareness and further evaluation of such features as non-standard variants. A discussion of theoretical issues is followed by the presentation of empirical data from a speech perception study (in the style of Herrgen/Schmidt 1985). Scale-based judgments by Northern, Central and Southern German listeners provide evidence about the subjective dialectality of 15 Bavarian regionalisms. They further reveal how subjective dialectality is related to listeners’ origins and regional language competence. Comparing the subjective data with two Bavarian speakers’ language use reveals the relation between subjective dialectality and synchronic variation in the analysed regionalisms.